Big machines - Wallace, Karen (New York : DK Pub., 2000)
Demonstrates how the crane, bulldozer, dump truck, and other construction machines all play a part in building a new park.
"Preschool-Grade 1"
Keywords: Construction equipment -- Juvenile literature; Construction equipment; Machinery